THE RELEVANCE OF MORALITY IN MODERN LEADERSHIP: A MORAL PHLOSOPHY ANALYSIS OF LEADERSHIP ETHICS - Marhamah, Siti (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2025)
This study examines the relevance of morality in modern leadership by highlighting how moral principles can shape ethical leadership with integrity and justice. This study aims to analyze the contribution of moral values to the formation of ethical leadership that is oriented towards the common welfare. The method used is a qualitative approach with a literature review of moral philosophy literature, including Aristotle's thoughts on virtue, Immanuel Kant's deontological ethics, and moral principles in the Islamic tradition. The theoretical framework in this study focuses on the relationship between individual morality and its influence on effective leadership. The results of the study indicate that moral-based leadership, which emphasizes honesty, responsibility, justice, and wisdom, plays a role in building legitimacy and public trust in leaders. In addition, this study found that the application of ethical leadership based on morality can be a solution to contemporary leadership problems, such as corruption, degrading power, and moral crises.